Modular Cooperative Learning: A New Approach In Teaching Mathematics - Cabrera, Freddie Revilla (International Journal of Advanced Science and Technology, 2020)
Various studies have indicated the effectiveness of the modular and cooperative learning approaches in promoting learning. With this, combining the two may further result to better learning. Innovations such as this can be used to further achieve the aims of Outcomes-based Education in higher education. This study aims to determine the effect of the modular and cooperative learning approaches when combined together for teaching College Algebra.Using the quasi-experimental design, respondents were composed of BSCS freshmen: 30 students for the experimental group taught using the modular cooperative learning and 30 students also to the control group who were taught using the conventional lecture-discussion method. The study employed the pre-test and post-test to determine the respondents’ performance before and after the intervention , mathematics achievement to determine their mathematics performance and  Mathematics attitude inventory test to determine their attitudes towards mathematics before and after the intervention.  A module was also developed for the purpose of this study. Scores were compared afterwards and the t-test was used to determine the significance of the differences.Results indicated that modular cooperative learning has a positive impact on the performance of the students in Mathematics. There was also a significant difference between modular cooperative learning and the traditional approach of lecture-discussion. This implies that learning improves if educators become more creative and innovative in shifting from teacher-centered to learner-centered classroom setups. With this, teachers will be able to apply the principles of Outcomes-based Education and equip students with the necessary skills the 21st Century demands from them.